Reimagining Critical Information Literacy as Creative Resistance - Feenstra, Kyle (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Drawing on the work of critical pedagogy scholars Paula Allman and Henry Giroux, this paper argues that reimagining information literacy as a critical epistemology requires a theory of learning capable of countering both the economic rationality and positivist assumptions that structure schooling and curriculum. For these reasons there is cause to revisit the implications of Paulo Freire’s pedagogy for critical information literacy. Freire’s interpretation of Marx’s dialectic, which is largely overlooked in Library and Information Sciences, supports a theory of resistance where an awareness of their immersion in antagonistic relations provide the foundation from which students and librarian-educators can deepen their understanding of the way information and education mediate experiences of social and political domination. As Freire argued, creatively reimagining and transforming literacy requires moving beyond the stage of social critique into an equitable form of dialogue where students and educators can construct authentic ways of knowing and being that humanize themselves and their world.